The Origins of Happiness : The Science of Well-Being over the Life Course - Clark, Andrew E.; Ward, George; Powdthavee, Nick; Layard, Richard, 1934-; Fleche, Sarah (Book collections on Project MUSE., 2019)
"What makes people happy? Why should governments care about people's well-being? How would policy change if well-being was the main objective? The Origins of Happiness seeks to revolutionize how we think about human priorities and to promote public policy changes that are based on what really matters to people. Drawing on a uniquely comprehensive range of evidence from longitudinal data on over one hundred thousand individuals in Britain, the United States, Australia, and Germany, the authors consider the key factors that affect human well-being. The authors explore factors such as income, education, employment, family conflict, health, childcare, and crime -- and their findings are not what we might expect. Contrary to received wisdom, income inequality accounts for only two percent or less of the variance in happiness across the population; the critical factors affecting a person's happiness are their relationships and their mental and physical health. More people are in misery due to mental illness than to poverty, unemployment, or physical illness. Examining how childhood influences happiness in adulthood, the authors show that academic performance is a less important predictor than emotional health and behavior, which is shaped tremendously by schools, individual teachers, and parents. For policymakers, the authors propose new forms of cost-effectiveness analysis that places well-being at center stage. Groundbreaking in its scope and results, The Origins of Happiness offers all of us a new vision for how we might become more healthy, happy, and whole."--